Do all roads lead to Waterford? The codex BnF fr. 1822 and its context (Carte Romanze, 2021)
This contribution aims to offer new insights into the context of the manuscript Paris, Bibliothèque nationale de France, fr. 1822. Keith Busby has recently ascribed this miscellany of Old French moral texts (sole witness of Jofroi de Waterford’s translations) to the Irish city of Waterford. The paper discusses this hypothesis, focusing on the codicological and historical aspects of the manuscripts. Moreover, the article presents my research on the (probably Anglo-Norman) redaction of the Livre de Moralitez transmitted by the codex.